The smallpox report : vaccination and the romantic illness narrative - Wang, Fuson (University of Toronto Press, 2023)
"After the COVID-19 pandemic, vaccination has become synonymous with an opaque biopower that legislates compulsory immunization at a distance. Contemporary illness narratives have become outlets for distrust, misinformation, reckless denialism, and selfish noncompliance. In The Smallpox Report, Fuson Wang rewinds this contemporary impasse between physician and patient back to the Romantic-era origins of vaccination. The book offers a literary-historical account of smallpox vaccination, contending that the disease's eventual eradication in 1980 was as much a triumph of the literary imagination as it was an achievement of medical Enlightenment science. Wang traces our modern, pandemic-era crisis of vaccine hesitancy back to Edward Jenner's publication of his treatise on vaccination in 1798, the first rumblings of an anti-vaccination movement, and vaccination's formative literary history that included authors such as William Wordsworth, William Blake, John Keats, Mary Shelley, and Arthur Conan Doyle. The book concludes with a re-examination of the current deeply polarized and polarizing public discourse about vaccines in the face of the COVID-19 pandemic. By recovering the surprisingly literary genres of Romantic-era medical writing, The Smallpox Report models a new literary historical perspective on our own crises of vaccine refusal."--